Free Lunch and Ride Sharing: A New Business Model for Winter Sport Resorts - Riccardo Bonazzi; Michaël Poli; Patrick Kuonen (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
This paper proposes a new business model for winter sport resorts, by adopting a cluster approach. By following the guidelines for design research, we propose a new online service, which combines the notions of ridesharing and rebate. Ridesharing is often seen as a solution to reduce the number of cars in winter sport resorts, whereas the delivery of discount coupon has been used to increase the amount of customers. Hence, we propose to reward skiers that share a ride with coupons of complementary activities in the winter sport resorts. We describe our proposed service by describing its customer journey.
Keywords: L8; L9; 330; ridesharing; crowd sourcing; business model innovation; tourism